2002
DOI: 10.1046/j.1523-1755.2002.00268.x
|View full text |Cite
|
Sign up to set email alerts
|

L-Arginine deficiency and supplementation in experimental acute renal failure and in human kidney transplantation

Abstract: Both experimental and clinical data show that \L-Arg deficiency and endothelial dysfunction are pathomechanistically relevant in ARF. The data suggest a therapeutic potential for the administration of L-Arg in ARF and kidney transplantation, at least in patients receiving kidneys with shorter CIT and from younger donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
61
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 40 publications
4
61
0
4
Order By: Relevance
“…NOS substrate supplementation has beneficial effects on both blood pressure and renal disease in clinical trials (35,47,52) and in experimental models (12,14,27,32,40,42,50). In animals with ureteral obstruction, the administration of L-arginine increases GFR and renal blood flow to the postobstructed kidney and decreases the infiltration of macrophages of the renal parenchyma (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NOS substrate supplementation has beneficial effects on both blood pressure and renal disease in clinical trials (35,47,52) and in experimental models (12,14,27,32,40,42,50). In animals with ureteral obstruction, the administration of L-arginine increases GFR and renal blood flow to the postobstructed kidney and decreases the infiltration of macrophages of the renal parenchyma (29).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced levels of L-arginine have been observed in renal failure, but the clinical relevance is uncertain, as the measured serum concentrations are well in excess of the K m for eNOS (1,38). Nevertheless, both clinical (20,47,52,60) and experimental studies (12,14,18,22,23,36,44) have demonstrated that substrate supplementation stimulates NO production and attenuates renal damage and salt-sensitive hypertension. Furthermore, chronic NO inhibition with N G -nitro-Larginine methyl ester (L-NAME), an antagonist for L-arginine, causes salt-sensitive hypertension and the development of renal injury (62).…”
mentioning
confidence: 99%
“…NO production is dependent on the activities of NOS enzymes, whose expression is, in turn, modulated by signaling pathways implicated in inflammation, such as NF-B and MAPKs (9 -11, 13, 14). NO donors protect the kidney in diverse models of renal failure, including ischemic renal failure (15,16), obstructive nephropathy (17), or renal allografts (18). Inhibition of NO synthesis increases susceptibility to kidney ischemia (16,19,20).…”
mentioning
confidence: 99%
“…Given the multiple functions of arginine 1,2,21 and the fact that a number of therapeutic approaches have been based on alterations in arginine availability, 6,7 it is of importance to investigate the longer-term homeostatic mechanisms elicited in response to a prolonged period of dietary deprivation of arginine and of its major immediate precursors. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4 An arginine deficiency impairs B cell maturation, 5 and supplementation or restriction of arginine intake have been advocated as therapeutic modalities for different pathophysiologic conditions. 6,7 Despite the functional and physiological significance of arginine, the whole body response and the homeostatic mechanisms elicited during a "long term" dietary restriction of arginine and its immediate metabolic precursors (proline, glutamate and aspartate), have not been previously investigated in healthy adults. Therefore, we have examined whole body, in vivo homeostasis of arginine in healthy adults under conditions of a long term (4 weeks) restriction of dietary arginine and its major precursors (ornithine, proline, glutamate and aspartate).…”
Section: Introductionmentioning
confidence: 99%